Exploring factors shaping consumer behaviour towards circular fashion: a focus on Generations Y and Z - Abdelmeguid, Aya; Afy-Shararah, Mohamed; Salonitis, Konstantinos (Frontiers in Sustainability, 2025)
The fashion industry faces significant challenges due to its linear systems and environmental impact. As sustainability gains priority among consumers, especially Generations Y and Z, the industry is urged to transition towards a circular economy. Despite this, the ‘attitude-behaviour gap’ persists, indicating minimal impact on consumer behaviour. This study explores factors influencing consumer behaviour towards circular fashion, focusing on Generations Y and Z. Nine hypotheses were developed, exploring relationships among environmental awareness, circular fashion awareness, willingness to change, willingness to pay a premium, and circular behaviour. Online surveys yielded 408 responses from participants from developing and developed countries. Structural Equation Modelling (SEM) was used for hypothesis testing. Results show consumer behaviour is influenced by environmental awareness and circular fashion awareness, and willingness to change. Additionally, purchasing decisions are driven by product quality and durability. The findings assist fashion businesses in aligning strategies with consumer perception among Generations Y and Z.